2023
DOI: 10.1021/acs.jcim.3c01533
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Pose Prediction Accuracy in RNA–Ligand Docking

Rupesh Agarwal,
Rajitha Rajeshwar T.,
Jeremy C. Smith

Abstract: Structure-based virtual high-throughput screening is used in early-stage drug discovery. Over the years, docking protocols and scoring functions for protein−ligand complexes have evolved to improve the accuracy in the computation of binding strengths and poses. In the past decade, RNA has also emerged as a target class for new small-molecule drugs. However, most ligand docking programs have been validated and tested for proteins and not RNA. Here, we test the docking power (pose prediction accuracy) of three s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…A recent study conducted by Agarwal et al showed that rDOCK, a RNA–ligand docking method, outperformed AutoDock Vina in pose prediction . However, in another study conducted by Jiang et al, protein–ligand docking tools showed more promising performance than RNA–ligand docking methods .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by Agarwal et al showed that rDOCK, a RNA–ligand docking method, outperformed AutoDock Vina in pose prediction . However, in another study conducted by Jiang et al, protein–ligand docking tools showed more promising performance than RNA–ligand docking methods .…”
Section: Introductionmentioning
confidence: 99%